Hubungan Kebiasaan Sarapan, Jajan Dan Faktor Lainnya Terhadap Kejadian Obesitas Anak Usia Sekolah - Amelya Fitri Yudhistira Hartono; Nunung Cipta Dainy (Program Studi Gizi UNSIKA, 2023)
The incidence of obesity, according to the World Health Organization (WHO), in 2011 estimated that in the world, there are about 1.6 billion adolescents aged 15 years overweight. As many as 400 million people are obese. This study aims to determine the correlation between diet, snacking habits, and other obesity-related factors in elementary school children. The research design used was an observational study design with a cross-sectional approach. The sampling technique for each class in this study used a proportional sampling technique. The results showed that 55% of students were obese. Most obese respondents have a habit of rarely having breakfast with a percentage of 66.6%, often snacking, with a rate of 50%, and rarely bringing lunch, with a share of 58.6%. Respondents who were obese had sufficient energy intake, with a percentage of 53.6%, and physical activity at a low level, with a rate of 75%. All research variables have a p-value <0.05, so the factors of breakfast habits, snacks, bringing lunch, energy intake, and physical activity are significantly related to the incidence of obesity in students of SDN Kebon Kosong 17 PG. Keywords: Breakfast Habits and Snacking Habits, Obesity, School Children